A method for preparing a spherical pitch-based hard carbon and a sodium-ion battery

CN120463195BActive Publication Date: 2026-10-09INST OF COAL CHEM CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510738642.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-04
Publication Date
2026-10-09
Estimated Expiration
2045-06-04

AI Technical Summary

Technical Problem

[0003]本发明针对目前沥青基硬炭从外向内氧化、活化造成的反应不均匀、皮芯结构难题,以中温沥青为原材料,利用沥青可熔融的特点,与金属盐熔融混合并发生配位反应,实现金属盐在沥青中的均匀分布和锚定;其次通过沥青成球缩聚反应制备沥青微球,可以提高材料压实密度;再通过金属盐的微活化作用,在沥青内部,从内向外实现造孔作用,利用大量的闭孔提高沥青基硬炭比容量;最后通过催化剂提前包埋,在高温炭化阶段进行同步催化石墨化,提高沥青基硬炭导电性的同时进一步增加压实密度,提升沥青基硬炭的体积能量密度

Benefits of technology

[0028]The preparation method of this invention is simple and easy to implement. The pitch-based hard carbon prepared by this method has a uniform spherical morphology and abundant closed pores, providing ample sodium storage space for sodium ions, thereby greatly improving the energy density and compaction density of the pitch-based hard carbon, and realizing the low-cost preparation of high-compact, high-energy pitch-based hard carbon anode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120463195B_ABST
    Figure CN120463195B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of spherical pitch-based hard carbon and a sodium ion battery, and belongs to the technical field of battery materials. In view of the problems of low compaction density and poor energy density of traditional hard carbon, pitch, metal salt and a balling agent are melt-blended, and low-temperature coordination is sequentially performed to make the pitch in a low-temperature melting state coordinate with the metal salt to realize uniform distribution and anchoring of the pitch inside; polycondensation, balling and catalyst embedding are performed, and a large amount of alkali metal vapor is released through micro-activation treatment to realize etching and pore making on the carbon structure; high-temperature carbonization treatment is performed to obtain the spherical pitch-based hard carbon with a solid structure and uniform particle size distribution. The preparation method is simple and easy to implement, the pitch-based hard carbon prepared through the preparation method has uniform spherical morphology and rich closed pores, provides rich sodium storage space for sodium ions, and thus greatly improves the energy density and compaction density of the pitch-based hard carbon, and realizes low-cost preparation of the pitch-based hard carbon negative electrode material with high compaction and high energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery materials technology, specifically relating to a method for preparing spherical pitch-based hard carbon and a sodium-ion battery. Background Technology

[0002] Sodium-ion batteries, as a novel energy storage device, have advantages such as low production cost, good rate performance, and strong environmental adaptability, making them a hot topic in the energy storage industry in recent years. Hard carbon, as the optimal solution for the anode of sodium-ion batteries, is a core material related to the energy density, power density, and cost of sodium-ion batteries. Traditional hard carbon anode materials are mostly biomass-based, but the naturally loose structure of biomass leads to poor durability, low compaction density, and high carbon yield and cost, limiting the further development of sodium-ion batteries. Asphalt, as a high-quality carbon material precursor, has advantages such as high carbon yield, strong processability, and low price. Patent CN119263279A discloses an asphalt-based closed-cell carbon material, its preparation method, and a sodium-ion battery. The preparation method includes pre-oxidation treatment, low-temperature carbonization treatment, gas activation treatment, chemical activation treatment, and coating treatment of the asphalt-based carbon source. The prepared asphalt-based closed-cell carbon material has the advantages of high capacity, high initial efficiency, and high stable cycle performance. CN115535996B authorizes a specific microcrystalline structure of pitch-based hard carbon, its preparation method, and its application. The preparation method includes: screening pitch raw materials, pre-oxidation crosslinking treatment, and carbonization treatment. Temperature control of the pre-oxidation crosslinking process optimizes the microcrystalline structure of the pitch-based hard carbon. These works demonstrate the feasibility of pitch-based hard carbon, but most employ an outside-to-inside oxidation crosslinking and activation method. Due to the inherent physicochemical properties of pitch, it easily forms a core-skin structure. The outside-to-inside oxidation and activation strategies mostly affect the surface layer, with little impact on the internal structure. Furthermore, previous works have largely focused on mass energy density, paying little attention to the volumetric density, which is more important to industry. Therefore, this invention, through processes such as melt mixing, micro-activation, and surface embedding catalytic graphitization, fuses metal salts with pitch, altering the pitch structure from the inside out. This results in more uniform activation, higher compaction density, and is more suitable for the technical requirements of sodium-ion batteries. Summary of the Invention

[0003] This invention addresses the challenges of uneven reaction and core-skin structure caused by the external-to-internal oxidation and activation processes in current asphalt-based hard carbon technology. Using medium-temperature asphalt as raw material, it leverages the fusibility of asphalt to melt and mix with metal salts, resulting in a coordination reaction that achieves uniform distribution and anchoring of the metal salts within the asphalt. Secondly, asphalt microspheres are prepared through a spheroidizing and condensing reaction, increasing the material's compaction density. Thirdly, the micro-activation effect of the metal salts creates pores from the inside out within the asphalt, increasing the specific capacity of the asphalt-based hard carbon through numerous closed pores. Finally, pre-embedding a catalyst allows for simultaneous catalytic graphitization during the high-temperature carbonization stage, improving the conductivity of the asphalt-based hard carbon while further increasing its compaction density and volumetric energy density. The resulting material, used as the negative electrode, produces sodium-ion batteries with advantages such as high specific capacity, high coulombic efficiency, and high volumetric energy density.

[0004] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0005] A spherical pitch-based hard carbon, wherein the spherical pitch-based hard carbon has a uniform spherical morphology and a particle size of 10~20μm;

[0006] The specific surface area of ​​the spherical pitch-based hard carbon is 2~10m². 2 / g;

[0007] The spherical pitch-based hard carbon has a specific capacity of 300~317mAh / g, an initial efficiency of 90~92%, and a compaction density of 1.00~1.06g / cm³. 3 .

[0008] A method for preparing spherical pitch-based hard carbon includes the following steps:

[0009] Step 1: Mix asphalt with metal salt and balling agent and place in a reaction vessel. Heat to melt the asphalt and hold for 10-30 minutes, stirring to ensure uniform mixing. Then continue heating to the low-temperature coordination temperature to promote the reaction and coordination of metal salt with asphalt, achieving uniform distribution and anchoring of metal salt within the asphalt.

[0010] Step 2: Further raise the temperature of the reactor to the polycondensation temperature, and carry out the reaction for 2-5 hours under an inert gas atmosphere with stirring;

[0011] Step 3: 30-60 minutes before the end of the polycondensation reaction in step 2, add a catalyst for encapsulation to obtain spherical asphalt;

[0012] Step 4: Place the spherical asphalt in a crucible and place it in a tube furnace for micro-activation treatment to obtain activated material;

[0013] Step 5: Place the activated material in a crucible and place it in a tube furnace for high-temperature carbonization to obtain spherical pitch-based hard carbon.

[0014] Furthermore, the asphalt is one of coal tar pitch, vacuum residue pitch, catalytic cracking slurry pitch, and ethylene tar pitch; the softening point of the asphalt is 90~120℃, and the quinoline insoluble content is 1~5%.

[0015] The metal salt is one of ZnCO3, K2CO3, and Na2CO3;

[0016] The pelletizing agent is one of carbon black, polystyrene microspheres, and ZnO;

[0017] The mass ratio of asphalt:metal salt:balling agent is 1:1~2:0.01~0.1;

[0018] Furthermore, the stirring speed in step 1 to mix the ingredients evenly is 10~30 r / min;

[0019] In step 1, the low-temperature coordination temperature is 200~250℃; in step 2, the polycondensation temperature is 300~400℃.

[0020] Furthermore, the inert gas atmosphere is either nitrogen or argon.

[0021] Furthermore, the stirring speed for mixing in step 1 to ensure uniform mixing is 10-30 r / min;

[0022] In step 2, the stirring speed during the reaction is 5-20 r / min.

[0023] Furthermore, the catalyst is one or a mixture of two of the following metal powders: Fe, Mg, Ca, and Cu, with a mass ratio of metal powder to asphalt of 0.01 to 0.05:1.

[0024] Furthermore, in step 4, the heating rate of the micro-activation treatment is 2~10℃ / min, the constant temperature is 800-950℃, the constant temperature time is 2-5h, and the atmosphere is a nitrogen atmosphere.

[0025] Furthermore, in step 5, the heating rate of the high-temperature carbonization treatment is 2~10℃ / min, the constant temperature is 1200~1400℃, the constant temperature time is 2~5h, and the atmosphere is a nitrogen atmosphere.

[0026] A sodium-ion battery, wherein the negative electrode of the sodium-ion battery comprises pitch-based hard carbon prepared by the aforementioned preparation method.

[0027] Compared with the prior art, the present invention has the following advantages:

[0028] The preparation method of this invention is simple and easy to implement. The pitch-based hard carbon prepared by this method has a uniform spherical morphology and abundant closed pores, providing ample sodium storage space for sodium ions, thereby greatly improving the energy density and compaction density of the pitch-based hard carbon, and realizing the low-cost preparation of high-compact, high-energy pitch-based hard carbon anode materials. Attached Figure Description

[0029] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0030] Figure 1 Scanning electron microscope image of spherical pitch-based hard carbon. Detailed Implementation

[0031] To gain a deeper understanding of this invention, we will provide a comprehensive and detailed description. However, this invention has various implementations and is not limited to the specific examples listed herein. These examples are presented to enhance a full understanding of the disclosure of this invention.

[0032] Example 1

[0033] This embodiment provides a method for preparing high-purity pitch-based hard carbon based on coal tar pitch condensation and impurity removal, and a sodium-ion battery, including the following steps:

[0034] Step 1: Coal tar pitch with a softening point of 90℃ and a quinoline insoluble content of 1% is mixed with ZnCO3 and carbon black and placed in a reaction vessel, wherein ZnCO3:pitch = 1:1 and carbon black:pitch = 0.01:1. The mixture is heated until the pitch melts and then held for 10 minutes. The mixture is stirred to make it uniform, and the stirring speed is 10 r / min. Then the temperature is further increased to the low-temperature coordination temperature of 200℃ to promote the reaction and coordination of ZnCO3 with pitch, so as to achieve uniform distribution and anchoring of ZnCO3 inside the pitch.

[0035] Step 2: Further increase the temperature of the reactor to the polycondensation temperature of 400℃, and carry out the reaction for 2 hours under an argon atmosphere with stirring at a stirring speed of 20 r / min.

[0036] Step 3: 30 minutes before the end of the constant temperature period, Fe powder is added for embedding. The ratio of Fe powder to asphalt is 0.01:1, resulting in spherical asphalt.

[0037] Step 4: Place the spherical asphalt in a crucible and place it in a tube furnace for micro-activation treatment. The heating rate is 2℃ / min, the constant temperature is 800℃, the constant temperature time is 5h, and the atmosphere is nitrogen to obtain the activated material.

[0038] Step 5: Place the activated material in a crucible and place it in a tube furnace for high-temperature carbonization treatment. The heating rate is 2℃ / min, the constant temperature is 1200℃, the constant temperature time is 5h, and the atmosphere is nitrogen atmosphere to obtain spherical pitch-based hard carbon.

[0039] The prepared spherical pitch-based hard carbon particles have a diameter of approximately 10 μm and a specific surface area of ​​2 m². 2 / g; compacted density is 1.00 g / cm³ 3 A sodium-ion battery was prepared using spherical pitch-based hard carbon as the negative electrode material. The specific capacity of the prepared battery was 300 mAh / g, and the initial efficiency was 90%.

[0040] Example 2

[0041] Step 1: Ethylene tar pitch with a softening point of 120℃ and a quinoline insoluble content of 5% is mixed with Na2CO3 and ZnO and placed in a reaction vessel, wherein the ratio of metal salt to pitch is 2:1 and the ratio of pelletizing agent to pitch is 0.1:1. The mixture is heated until the pitch melts and then held for 30 minutes. The mixture is stirred at a speed of 30 r / min to ensure uniform mixing. Then the temperature is raised to the low-temperature coordination temperature of 250℃ to promote the reaction and coordination of Na2CO3 with pitch, thereby achieving uniform distribution and anchoring of Na2CO3 within the pitch.

[0042] Step 2: Further increase the temperature of the reactor to the polycondensation temperature of 300°C, and carry out the reaction for 5 hours under either nitrogen or argon atmosphere with stirring at a stirring speed of 5 r / min.

[0043] Step 3: 60 minutes before the end of the constant temperature period, add Cu powder for embedding. The ratio of Cu powder to asphalt is 0.05:1, to obtain spherical asphalt.

[0044] Step 4: Place the spherical asphalt in a crucible and place it in a tube furnace for micro-activation treatment. The heating rate is 10℃ / min, the constant temperature is 950℃, the constant temperature time is 2h, and the atmosphere is nitrogen to obtain the activated material.

[0045] Step 5: Place the activated material in a crucible and place it in a tube furnace for high-temperature carbonization treatment. The heating rate is 10℃ / min, the constant temperature is 1400℃, the constant temperature time is 2h, and the atmosphere is nitrogen atmosphere to obtain spherical pitch-based hard carbon.

[0046] The prepared spherical pitch-based hard carbon particles have a diameter of approximately 20 μm and a specific surface area of ​​10 m². 2 / g; compacted density is 1.06g / cm³ 3 A sodium-ion battery was prepared using spherical pitch-based hard carbon as the negative electrode material. The specific capacity of the prepared battery was 305 mAh / g, and the initial efficiency was 91.2%.

[0047] Example 3

[0048] Step 1: Vacuum residue asphalt with a softening point of 105℃ and a quinoline insoluble content of 2% is mixed with K2CO3 and polystyrene microspheres and placed in a reaction vessel. The ratio of metal salt to asphalt is 1.5:1, and the ratio of sphere forming agent to asphalt is 0.04:1. The mixture is heated until the asphalt melts and then held for 20 minutes. The mixture is stirred at a speed of 15 r / min to ensure uniform mixing. The temperature is then increased to the low-temperature coordination temperature of 250℃ to promote the reaction and coordination of K2CO3 with the asphalt, thereby achieving uniform distribution and anchoring of K2CO3 within the asphalt.

[0049] Step 2: Further increase the temperature of the reactor to the polycondensation temperature of 350°C, and carry out the reaction for 3 hours under a nitrogen atmosphere with stirring at a stirring speed of 15 r / min.

[0050] Step 3: 30 minutes before the end of the constant temperature period, add a mixture of Fe and Ca metal powders for embedding. The ratio of Fe to Ca is 1:1, and the ratio of metal powder to asphalt is 0.05:1, to obtain spherical asphalt.

[0051] Step 4: Place the spherical asphalt in a crucible and place it in a tube furnace for micro-activation treatment. The heating rate is 5℃ / min, the constant temperature is 900℃, the constant temperature time is 3h, and the atmosphere is nitrogen to obtain the activated material.

[0052] Step 5: Place the activated material in a crucible and place it in a tube furnace for high-temperature carbonization treatment. The heating rate is 5℃ / min, the constant temperature is 1300℃, the constant temperature time is 3h, and the atmosphere is nitrogen atmosphere to obtain spherical pitch-based hard carbon.

[0053] The prepared spherical pitch-based hard carbon particles have a particle size distribution of approximately 18 μm and a specific surface area of ​​7 m². 2 / g; compacted density is 1.04 g / cm³ 3 A sodium-ion battery was prepared using spherical pitch-based hard carbon as the negative electrode material. The specific capacity of the prepared battery was 317 mAh / g, and the initial efficiency was 90.8%.

[0054] Example 4

[0055] Step 1: Catalytic cracking slurry asphalt with a softening point of 95℃ and a quinoline insoluble content of 3% is mixed with K2CO3 and carbon black and placed in a reactor, wherein K2CO3:asphalt = 1.25:1 and carbon black:asphalt = 0.06:1. The mixture is heated until the asphalt melts and held for 20 minutes. It is then stirred to ensure uniform mixing at a stirring speed of 20 r / min. The temperature is then increased to the low-temperature coordination temperature of 220℃ to promote the reaction and coordination of K2CO3 with the asphalt, thereby achieving uniform distribution and anchoring of metal salts within the asphalt.

[0056] Step 2: Further increase the temperature of the reactor to the polycondensation temperature of 400℃, and carry out the reaction for 4 hours under a nitrogen atmosphere with stirring at a stirring speed of 15 r / min.

[0057] Step 3: 30-60 minutes before the end of the constant temperature period, add a mixture of Mg and Cu metal powders for embedding. The ratio of Mg to Cu is 0.5:1, and the ratio of metal powder to asphalt is 0.02:1, to obtain spherical asphalt.

[0058] Step 4: Place the spherical asphalt in a crucible and place it in a tube furnace for micro-activation treatment. The heating rate is 4℃ / min, the constant temperature is 850℃, the constant temperature time is 4h, and the atmosphere is nitrogen to obtain the activated material.

[0059] Step 5: Place the activated material in a crucible and place it in a tube furnace for high-temperature carbonization treatment. The heating rate is 4℃ / min, the constant temperature is 1250℃, the constant temperature time is 4h, and the atmosphere is nitrogen atmosphere to obtain spherical pitch-based hard carbon.

[0060] The prepared spherical pitch-based hard carbon particles have a particle size distribution of approximately 15 μm and a specific surface area of ​​5 m². 2 / g; compacted density is 1.03g / cm³ 3 A sodium-ion battery was prepared using spherical pitch-based hard carbon as the negative electrode material. The specific capacity of the prepared battery was 307 mAh / g, and the initial efficiency was 92%.

[0061] Example 5

[0062] Step 1: Catalytic cracking slurry asphalt with a softening point of 110℃ and a quinoline insoluble content of 2.5% is mixed with Na2CO3 and polystyrene microspheres and placed in a reactor, wherein Na2CO3:asphalt = 2:1 and polystyrene microspheres:asphalt = 0.1:1. The mixture is heated to the point where the asphalt melts and held for 30 minutes. The mixture is stirred at a speed of 30 r / min to ensure uniform mixing. Then, the temperature is raised to the low-temperature coordination temperature of 250℃ to promote the reaction and coordination of Na2CO3 with the asphalt, thereby achieving uniform distribution and anchoring of metal salts within the asphalt.

[0063] Step 2: Further increase the temperature of the reactor to the polycondensation temperature of 400℃, and carry out the reaction for 3 hours under either nitrogen or argon atmosphere with stirring at a stirring speed of 20 r / min.

[0064] Step 3: 60 minutes before the end of the constant temperature period, a mixture of Fe and Cu metal powders is added for embedding. The ratio of Fe to Cu is 0.75:1, and the ratio of metal powder to asphalt is 0.05:1, to obtain spherical asphalt.

[0065] Step 4: Place the spherical asphalt in a crucible and place it in a tube furnace for micro-activation treatment. The heating rate is 2℃ / min, the constant temperature is 900℃, the constant temperature time is 2h, and the atmosphere is nitrogen to obtain the activated material.

[0066] Step 5: Place the activated material in a crucible and place it in a tube furnace for high-temperature carbonization treatment. The heating rate is 2℃ / min, the constant temperature is 1300℃, the constant temperature time is 2h, and the atmosphere is nitrogen atmosphere to obtain spherical pitch-based hard carbon.

[0067] The prepared spherical pitch-based hard carbon particles have a particle size distribution of 15 μm and a specific surface area of ​​6 m². 2 / g; compacted density is 1.02g / cm³ 3 A sodium-ion battery was prepared using spherical pitch-based hard carbon as the negative electrode material. The specific capacity of the prepared battery was 312 mAh / g, and the initial efficiency was 90.2%.

[0068] Table 1 Material Properties of Examples

[0069]

[0070] Contents not described in detail in this specification are prior art known to those skilled in the art. Although illustrative specific embodiments of the invention have been described above to facilitate understanding by those skilled in the art, it should be understood that the invention is not limited to the scope of the specific embodiments. Various modifications are readily apparent to those skilled in the art as long as they fall within the spirit and scope of the invention as defined and determined by the appended claims, and all inventions utilizing the concept of this invention are protected.

Claims

1. A method for preparing spherical pitch-based hard carbon, characterized in that: Includes the following steps: Step 1: Mix asphalt with metal salt and balling agent and place in a reaction vessel. Heat to melt the asphalt and hold for 10-30 minutes, stirring to ensure uniform mixing. Then continue heating to the low-temperature coordination temperature to promote the reaction and coordination of metal salt with asphalt, achieving uniform distribution and anchoring of metal salt within the asphalt. Step 2: Further raise the temperature of the reactor to the polycondensation temperature, and carry out the reaction for 2-5 hours under an inert gas atmosphere with stirring; Step 3: 30-60 minutes before the end of the polycondensation reaction in step 2, add a catalyst for encapsulation to obtain spherical asphalt; Step 4: Place the spherical asphalt in a crucible and place it in a tube furnace for micro-activation treatment to obtain activated material; Step 5: Place the activating material in a crucible and place it in a tube furnace for high-temperature carbonization to obtain spherical pitch-based hard carbon. The metal salt is one of ZnCO3, K2CO3, and Na2CO3; The pelletizing agent is one of carbon black, polystyrene microspheres, and ZnO; The spherical pitch-based hard carbon has a uniform spherical morphology and a particle size of 10~20μm; The specific surface area of ​​the spherical pitch-based hard carbon is 2~10m². 2 / g; The spherical pitch-based hard carbon has a specific capacity of 300~317mAh / g, an initial efficiency of 90~92%, and a compaction density of 1.00~1.06g / cm³. 3 .

2. The method for preparing spherical pitch-based hard carbon according to claim 1, characterized in that: The asphalt is one of coal tar pitch, vacuum residue pitch, catalytic cracking slurry pitch, and ethylene tar pitch; the softening point of the asphalt is 90~120℃, and the quinoline insoluble content is 1~5%; The mass ratio of asphalt:metal salt:balling agent is 1:1~2:0.01~0.

1.

3. The method for preparing spherical pitch-based hard carbon according to claim 1, characterized in that: In step 1, the stirring speed to mix the ingredients evenly is 10~30 r / min; In step 1, the low-temperature coordination temperature is 200~250℃; in step 2, the polycondensation temperature is 300~400℃.

4. The method for preparing spherical pitch-based hard carbon according to claim 1, characterized in that: The inert gas atmosphere is either nitrogen or argon.

5. The method for preparing spherical pitch-based hard carbon according to claim 1, characterized in that: The stirring speed in step 1 to mix the ingredients evenly is 10-30 r / min; In step 2, the stirring speed during the reaction is 5-20 r / min.

6. The method for preparing spherical pitch-based hard carbon according to claim 1, characterized in that: The catalyst is one or a mixture of two of the following metal powders: Fe, Mg, Ca, and Cu, with a mass ratio of metal powder to asphalt of 0.01 to 0.05:

1.

7. The method for preparing spherical pitch-based hard carbon according to claim 1, characterized in that: In step 4, the heating rate of the micro-activation treatment is 2~10℃ / min, the constant temperature is 800-950℃, the constant temperature time is 2-5h, and the atmosphere is nitrogen.

8. The method for preparing spherical pitch-based hard carbon according to claim 1, characterized in that: In step 5, the heating rate of the high-temperature carbonization treatment is 2~10℃ / min, the constant temperature is 1200~1400℃, the constant temperature time is 2~5h, and the atmosphere is nitrogen atmosphere.

9. A sodium-ion battery, characterized in that: The negative electrode of the sodium-ion battery includes pitch-based hard carbon prepared by the preparation method according to any one of claims 1-8.

Citation Information

Patent Citations

  • A specific microcrystalline structure asphalt-based hard carbon and its preparation method and application

    CN115535996B

  • Asphalt-based closed-pore carbon material, preparation method thereof and sodium ion battery

    CN119263279A

  • High-capacity lithium ion secondary battery cathode carbon material

    CN103094536A